IGNITING STUDENTS’ MOTIVATION IN WRITING THROUGH JOURNAL WRITING - Nita Maya Valiantien; Ririn Setyowati; Setya Ariani (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Until recent decades, the effort on diminishing students’ feeling of anxiety and less self-efficacy toward the writing activities in academic writing course still becomes a great concern for the teachers or practitioners of writing skill especially when dealing with students from multilingual society. These students, who learn English as a foreign language, often demonstrate the influence of their first language when composing a writing, even in a simple paragraph. Facing this situation, the teachers are forced to give attention more to students’ grammatical composition, and as a result of this most of the students give excessive attention only to revise the grammatical mistakes. Based on this situation, they develop “mental block” towards writing and have less interest in writing. To deal with this situation, many studies suggest that teachers need to foster students’ motivation since it is as crucial as developing students’ writing skills through practice. Hence, this paper aims to describe the effectiveness of giving journal writing task and providing comments to students’ writing in the task as a simple but useful way to ignite students’ motivation in writing. The object of the research is the students of academic writing course in Faculty of Cultural Studies of Mulawarman University Samarinda. List of questions were given to the students after they experienced the task to figure out how much the task and the comments influence students’ motivation in writing